P004 Altered colonic mucosal oxylipins and endocannabinoids levels in treatment-naive and deep remission ulcerative colitis patients. (16th January 2018) - Diab, J; Gouveia, S; Hansen, T; Jensen, E; Moritz, T; Goll, R; Florholmen, J; Forsdahl, G
Abstract: Background: The two major forms of inflammatory bowel disease (IBD), ulcerative colitis (UC) and Crohn's disease (CD), are characterised by a dysregulated mucosal immune response triggered by the intestinal flora. The pathobiology of IBD suggests that this immune response is caused by an imbalance between pro- and anti-inflammatory molecules. The bioactive metabolites of Omega-6 (ω-6) and Omega-3 (ω-3) polyunsaturated fatty acids (PUFAs) are known as oxylipins and endocannabinoids (eCBs). These metabolites are directly involved in provoking and resolving the inflammatory response. However, there is a scarcity of studies analysing the colonic mucosal levels of these bioactive metabolites in patients with IBD. Therefore, our study aims to define the inflammatory metabolic signatures of PUFAs in newly diagnosed treatment-naive and deep remission UC patients with reference to healthy controls. Methods: Colon biopsies were taken from 15 treatment-naive UC patients at the debut of the disease (inflamed mucosa), five UC patients in deep remission and 10 healthy subjects. The state of deep remission was defined by histological and immunological remission demonstrated by a normalised tumour necrosis factor gene expression. A total of 34 oxylipins and 11 eCBs were quantified by means of ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MSMS). Results: Among treatment-naive patients, the levels of ω-6-related oxylipins, specifically PGE2, TXB2, and 12-HETE, were significantly elevated (FDR < 0.1) with respect to healthy controls. Among UC deep remission patients, the level of the ω-6-related oxylipin, 15(s)-HETrE, was significantly higher (FDR < 0.1) with respect to healthy controls. Furthermore, the analysis of variance (ANOVA) made with Fisher LSD post hoc comparisons revealed significant differences in the levels of ω-3-related eCBs, docosahexaenoyl ethanolamine (DHEA) and eicosapentaenoyl ethanolamine (EPEA), between the study groups. Treatment-naive UC patients had the lowest detected levels of DHEA and EPEA compared with UC remission patients and healthy controls. Conclusions: To our knowledge, this is the first study reporting comprehensive characterisation of oxylipins and endocannabinoids in colon mucosa of untreated newly diagnosed and deep remission UC patients. High levels of ω-6-related oxylipins and low levels of ω-3-related endocannabinoids were found in inflamed colon mucosa. Our findings provide a further evidence of the altered balance between pro- and anti-inflammatory lipids mediators in UC. The mucosal fingerprints of the polyunsaturated fatty acid metabolism are potential biomarkers for UC progression and may be potential targets for intervention.